2010
DOI: 10.1166/jnn.2010.2625
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Crossing Through and Distribution in the Blood-Brain Barrier In Vitro

Abstract: Silver nanoparticles (SNPs) translocate to the brain through the blood stream after they are implanted in vivo. The aim of this study was to investigate the distribution of SNPs that crossed through the blood-brain barrier (BBB). An in vitro BBB model established by co-cultures of rat brain microvessel vascular endothelial cells (BMVECs) with astrocytes (ACs) was cultured with cell culture medium containing 100 microg/mL of either SNPs or silver microparticles (SMPs). After 4 hours of culture, the ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(74 citation statements)
references
References 0 publications
0
74
0
Order By: Relevance
“…It was demonstrated using an in vitro BBB model that AgNPs can pass the BBB mainly by transcytosis and accumulate inside endothelial cells of microvessels [134]. Moreover, there is evidence that AgNPs induce the release of IL-1β and TNF-α in rat brain microvessels and that this leads to inflammation and a subsequent increase in the permeability of the BBB [137].…”
Section: The Influence Of Agnps On Blood-brain Barrier Functionmentioning
confidence: 99%
“…It was demonstrated using an in vitro BBB model that AgNPs can pass the BBB mainly by transcytosis and accumulate inside endothelial cells of microvessels [134]. Moreover, there is evidence that AgNPs induce the release of IL-1β and TNF-α in rat brain microvessels and that this leads to inflammation and a subsequent increase in the permeability of the BBB [137].…”
Section: The Influence Of Agnps On Blood-brain Barrier Functionmentioning
confidence: 99%
“…24 Several studies have demonstrated that Ag-NPs can enter the CNS 25 and induce brain edema and neurotoxicity. 10,11,[26][27][28][29] Our previous studies showed that Ag-NPS and/or released Ag ions crossed the BBB and subsequently caused damage to astrocytes and neurons. 23 Cadherin and claudin expression were slightly changed in the Ag-NPS-exposure group, and astrocyte swelling was the most significant change after a 2-week gastrointestinal exposure to 1 mg/kg or 10 mg/kg of Ag-NPS in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, how Ag-NPs induce BBB dysfunction and neurotoxicity has been of particular interest, because Ag-NPs have been shown to enter the brain by crossing the BBB in vitro and in vivo. [7][8][9][10] Previous studies reported that intravenous or subcutaneous injection of Ag-NPs can induce BBB dysfunction, astrocyte swelling, and neuronal degeneration in rats. [7][8][9] The BBB permeability mechanisms of Ag-NPs were further investigated using an in vitro BBB model (cocultures of rat brain microvascular endothelial cells with astrocytes).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that silver nanoparticles (AgNPs) were able to be translocated by blood circulation and distributed throughout the main organs in the form of particles (Tang et al, 2009). Given that AgNPs are capable of permeating the tight blood-brain barrier (BBB) and entering the brain tissue (Tang et al, 2010), the issue on assessing the specific responses of neurons to AgNPs is of great relevance. Animal studies proved that intravenous injection of AgNPs in Sprague-Dawley (SD) rats caused the functional injury of central nervous system (CNS) by decreasing their locomotor activity (Zhang et al, 2013), showing the potential neurotoxicity of AgNPs.…”
Section: Introductionmentioning
confidence: 99%